USAGE PATTERN OF HOUSEHOLD DRINKING WATER IN DIARRHEA IN LAND OF BUMBU YEAR 2016 - Dicky Andiarsa; Syarif Hidayat; Ika Setianingsih (The Indonesian Journal of Public Health, 2020)
ABSTRACTDiarrhea has been long a public health concern in the world especially to infants and children. Diarrhea can be caused by many factors including sanitation, clean and healthy behavior, and access to clean water, consumption of drinking water and food, and so on. The results of the research in Tanah Bumbu Regency stated that some of the main causes related to the incidence of diarrhea in Tanah Bumbu Regency included Sanitation, Healthy and clean behavior, clean water access, and drinking water access. Secondary data analysis held to define the scheme of drinking water consumption in families with diarrhea patients in Tanah Bumbu Regency. The result showed that the most families with diarrhea consumed refill drinking water (67.06%) with most of them did not do any pre-treatment to the water (81.55%). The water consuming pattern has been changed to community of Tanah Bumbu Regency by consuming refilling water. Processing (boiling) refilling water before drinking can reduce the risk of diarrhea.Keywords: refilling drinking water, diarrhea, drinking water consumption patterns